Rosling Jemiron: “one of the most hardworking, deserving and efficient assistants " - Ng, Kui Choo (UiTM Sarawak, 2004)
Prof Madya Hajah Lelawati, Head of the Quality Unit, describes her as "one of the most hardworking, deserving and efficient assistants I have ever come across." And it did not take me long to find out why Lelawati was practically singing accolades of her. Soft-spoken Rosling from Unit Kualiti is one grateful person who has seen it all. She still recalls the years of anxiety and frustration as she attended interview after interview, trying to find herself a permanent position. She started out at UiTM as Penyelia Asrama in 1994. The daily paid job was not demanding; neither did it hold much promise for a forward-looking young lady. In 1998 she succeeded in landing another temporary and daily-paid position as Lab Assistant with Makmal Sains. She persevered and two years later, she was offered the post of Pembantu Tadbir with the Quality Unit where she remains to this day.